TÁLIM BASQA TILLERDE ALIP BARILATUǴIN MEKTEPLERDE QARAQALPAQ TILIN OQITIW MÁSELELERI - Bekimbetova, G.R. (ILIM hám JÁMIYET, 2023)
This article discusses the issues of teaching the Karakalpak language in educational institutions where education is conducted in other languages, the development of students’ language competencies.